Meningkatkan Keunggulan Kompetitif dengan Memilih Strategi Tingkat Bisnis yang Tepat - Diana Vimalakirti Chow; Hardi Suandri; Herman Herman; Prissilia Angelika; Ricky Ricky (Public Service and Governance Journal, 2023)
Currently in an environment full of competition, the use of competitive advantage for companies must be very agile and adaptive. While it is often unable to establish a certain level of performance based on existing technology advancements, companies also frequently tap into new emerging technologies. How to address business appropriately as a way for companies to simultaneously exploit their current competitive advantages while exploring opportunities for the future. This achievement is based on a balance between exploration and exploitation which consists of more than just allocating resources in proportion between the two processes. So as will be discussed, For exploration to exploitation is a process that should be, different structures and cultures.